Filogenia do subcomplexo Triatoma sordida (Hemiptera, Reduviidae, Triatominae), por meio de estudos morfológicos, morfométricos e moleculares - Beliintani, Tiago [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Triatoma garciabesi, Triatoma guasayana Triatoma patagonica and Triatoma sordida are the subcomplex T. sordida, triatomine bugs that can serve Trypanosoma cruzi and determine Chagas disease in humans. So because of the epidemiological importance was conducted this study may contribute to the control of these vectors. . So because of the epidemiological importance was conducted this study can contribute to the vector control. The phylogeny of the subcomplex T. sordida was conducted by the morphology of the median process pygophore, external female genitalia, histology eggs, morphometry eggs and geometric morphometric wings. Molecular markers were also used CO1, Cyt b, 16S, 28S, ITS1 and ITS2. The results corroborate the descriptions of literature and provide new parameters for the characterization of the four species of T. sordida subcomplex and the phylogenetic relationships of Triatominae. The study of median process of pygophore of T. garciabesi, T. guasayana and T. sordida by means of SEM showed no differences between the three species. The female external genitalia of T. garciabesi, T. guasayana, T. patagonica and T. sordida observed by SEM showed differences that make it possible to distinguish these species. The morphological study of eggs by SEM The morphological study of eggs by SEM enabled possible to describe the characteristics of the exochorion of the four species, but was not very effective for discrimination. The Histological study reveals differences in tissue constitution of the four species exochorion. The morphometric study of eggs show that the variables of length and opercular opening eggs feature significant differences between species, the variable width was not significant. By morphometry of the wings was possible to differentiate the species, the resulting values of centroid size, show differences in the size of the wings and consistent sexual dimorphism. Canonical variables resulted in seven variables, what explained 100% of the difference. The CV1 and CV2 showed greater discriminant power, generating clearly defined groupings. The variability in size and shape of the wings were observed for the values of the principal components. The values obtained from discriminant analysis made it possible to build a phenograms showing morphometric distances between species. The values of the discriminant analysis allowed building a phenogram showing the morphometric distances between species. The sequenced genes CO1, Cyt b, 16S and 28S. By maximum likelihood, it was possible to build filograma of genetic distance and the genes studied showed high values of bootstrap. The concatenation of CO1 gene, Cyt b, 16S and 28S through Bayesian inference separates species in four specific clades supported by high bootstrap values. The molecular analysis of genes for maximum likelihood and Bayesian inference with combined genes show that T. guasayana and T.patagonica differ from subcomplex species; species are relatively close to T. rubrovaria. The species T. sordida and T. garciabesi maintained the status of closely related species, The T. sordida feature variability but with genetic proximity. Given the difficulties of specific identification of T. sordida subcomplex. This work contributed to specific diagnosis, as well as for the phylogeny within the subfamily Triatominae. It is concluded that the morphological, molecular and morphometric studies were performed, were useful characterize the four species of subcomplex T. sordida as to suggest a new positioning for T. guasayana and T. patagonica. Keywords

Triatoma garciabesi, Triatoma guasayana, Triatoma patagonica e Triatoma sordida constituem o subcomplexo T. sordida, triatomíneos que podem veicular Trypanosoma cruzi e determinar doença de Chagas em humanos. Assim devido a importância epidemiológica foi conduzido este estudo que pode contribuir para o controle vetorial. A filogênese do subcomplexo T. sordida foi conduzido por meio de estudos do processo mediano do pigóforo, genitália externa feminina, histologia de ovos, morfometria de ovos e morfometria geométrica de asas. Também se utilizou dos marcadores moleculares CO1, Cyt b, 16S e 28S. Os resultados obtidos corroboram as descrições da literatura e fornecem novos parâmetros para a caracterização das quatro espécies do subcomplexo T. sordida, bem como das relações filogenéticas da subfamília Triatominae. O estudo do processo mediano do pigóforo de T. garciabesi, T. guasayana e T. sordida por meio de MEV não mostrou diferenças entre as três espécies. A genitália externa feminina de T. garciabesi, T. guasayana, T. patagonica e T. sordida observadas por MEV, apresentaram diferenças que possibilitam distinguir essas espécies. O estudo morfológico dos ovos por meio de MEV possibilitou descrever as características do exocório das quatro espécies, mas apresentou pouca eficácia para discriminação. O estudo histológico revelou diferenças na constituição tissular dos exocórios das quatro espécies. O estudo morfométrico de ovos mostrou que as variáveis de comprimento e abertura opercular dos ovos apresentam diferenças significativas entre as espécies, a variável largura não foi significativa. Por meio da morfometria das asas foi possível diferenciar as espécies e os valores resultantes do tamanho do centroide mostraram diferenças no tamanho das asas, assim como consistente dimorfismo sexual. As variáveis canônicas resultaram em sete variáveis que explicaram 100% das diferenças. A CV1 e CV2 apresentaram maior poder discriminante, gerando agrupamentos claramente definidos. A variabilidade de forma e tamanho das asas foram observadas pelos valores dos componentes principais. Os valores obtidos da análise discriminante possibilitou construir um fenograma que mostrou as distancias morfométricas entre as espécies. Foram sequenciados os genes CO1, Cyt b, 28S e 16S. Por meio de máxima-verossimilhança, foi possível construir filograma de distância genética e os genes estudados apresentaram valores altos de bootstrap. A concatenação dos genes CO1, Cyt b, 28S e 16S por meio de inferência bayesiana separou as espécies em quatro clados específicos suportados por elevados valores de bootstrap. As análises moleculares dos genes por máxima-verossimilhança e combinados na inferência bayesiana mostram que T. guasayana e T. patagonica divergem das espécies do subcomplexo, as espécies são relativamente próximas a T. rubrovaria. Triatoma sordida e T. garciabesi mantiveram o status de espécies próximas. As populações de T. sordida apresentaram variabilidade, mas com proximidade genética e morfológica. Dadas as dificuldades de identificação específica do subcomplexo T. sordida, este trabalho contribuiu para a diagnose específica, bem como para a filogenia dentro da subfamília Triatominae. Conclui-se que os estudos morfológicos, morfométricos e moleculares condunzidos foram úteis para caracterizar as quatro espécies do subcomplexo T. sordida, bem como para sugerir um novo posicionamento para T. guasayana e T. patagonica.
Phylogeny of the subcomplex Triatoma sordida (Hemiptera, Reduviidae, Triatominae), through morphological, morphometric and molecular studies
Keywords: Phylogeny; Triatomine; T. sordida subcomplex; Morphology; Morphometry; Molecular; Filogenia; Triatominae; Subcomplexo T. sordida; Morfologia; Morfometria; Molecular